(untitled) - Giammarco, Thomas (Thành phố Hồ Chí Minh, 2015)
Short-time learning with LC & RC in one volume Easy for beginners to understand the core lessons and apply them to a variety of exercises Step by step intrustion from theory to actual practice Extensive grammar points and examples of the latest trend as well as high-frequency questions
Keywords: Tiếng Anh,English language; Kỳ thi,Examinations